2012
DOI: 10.1097/sla.0b013e31826b4c4f
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical Registry Versus Administrative Claims Data for Reporting of 30-Day Surgical Complications

Abstract: Objectives:To compare the recording of 30-day postoperative complications between a national clinical registry and Medicare inpatient claims data and to determine whether the addition of outpatient claims data improves concordance with the clinical registry. Background: Policymakers are increasingly discussing use of postoperative complication rates for value-based purchasing. There is debate regarding the optimal data source for such measures. Methods: Patient records (2005)(2006)(2007)(2008) from the America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
226
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 315 publications
(233 citation statements)
references
References 12 publications
5
226
1
1
Order By: Relevance
“…The accuracy of documentation of clinical diagnoses, comorbidities, and complications collected in any database can be limited by errors in data entry. However, previous studies of the ACS-NSQIP 1 database have shown excellent accuracy and quality control because the database relies on clinical data from patients' medical charts gathered by skilled reviewers and does not rely on administrative claims or billing information [9,10,15,20]. The integrity of data collected is scrutinized through site visits at participating institutions, conference calls, an annual meeting of participants, and regular auditing.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of documentation of clinical diagnoses, comorbidities, and complications collected in any database can be limited by errors in data entry. However, previous studies of the ACS-NSQIP 1 database have shown excellent accuracy and quality control because the database relies on clinical data from patients' medical charts gathered by skilled reviewers and does not rely on administrative claims or billing information [9,10,15,20]. The integrity of data collected is scrutinized through site visits at participating institutions, conference calls, an annual meeting of participants, and regular auditing.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications contribute significantly to the risks of surgery and anaesthesia, with impact on discharge and financial repercussions on the health system [19]. The risk of perioperative complications depends on ASA (American Society of Anesthesiologists) class [20], age [21], emergency surgery, cardiac comorbidities [22], smoking [23], duration of surgery [24], type of anaesthesia [25], as well as on the presence of comorbidities such as chronic obstructive pulmonary disease, coronary artery disease, and renal failure [26].…”
Section: Discussionmentioning
confidence: 99%
“…10 This program has incorporated a wide range of surgical specialties and pediatric-specific comorbidities, procedures, and outcomes. In contrast to claims databases that rely on billing or administrative codes with potentially inconsistent clinical meaning, [11][12][13] the NSQIPPediatric utilizes trained personnel to prospectively collect comprehensive clinical data from the medical record. After establishing feasibility, 8,9 the NSQIP-Pediatric rapidly expanded to include more than 40 hospitals.…”
Section: Discussionmentioning
confidence: 99%